"THE WRECK OF THE DEUTSCHLAND" AS POETIC MANIFESTO - Lori-ann Bumstead (My University, 1988)
Gerard Manley Hopkins's poem, "The Wreck of the Deutschland", breaks forth from a fairly lengthy period of self-imposed poetic silence, during which the poet struggled to reconcile his literary interests with his priestly vocation. That "The Wreck..." was written at all attests to the resolution of the conflicts which had led Hopkins to give up poetry, but the poem must be recognized as much more than a physical indication of Hopkins's resolution. In this thesis I examine the poem as a kind of joyous poetic manifesto, proclaiming and celebrating Hopkins's new-found conviction that "poetry proper" could name God, and that he, as poet, could thus serve and glorify God. Hopkins's unique understanding of the Incarnation played a crucial role in his development of poetic theory, and this understanding shapes and informs "The Wreck of the Deutschland" as well. Stanzas five to eight in particular demonstrate Hopkins's conviction that divine inspiration, manifested in two distinct ways, could move a poet to "word" God, and that such divinely inspired utterances could in turn, inspire the "hearers" of the poem. Hopkins's ambitions as an agent in the re-conversion of his beloved England to Roman Catholicism are the source of the curiously ecstatic mood of the poem which is ostensibly written in commemoration of the five Franciscan nuns who drowned in the shipwreck off the coast of England "between midnight and morning of Dec. 7th, 1875" (Poems 51).